The potential of 99mTc-PEI-MP for diagnosis and 188Re-PEI-MP for therapy of bladder carcinoma - Ferreira, Sara (2015)
Introduction: The water-soluble polymer PEI-MP (polyethyleneimine, functionalised with methylphosphonate groups) that might be labeled with 188Re and 99mTc presents a strong potential for metabolic radiotherapy and diagnosis, respectively. The aim of this study was to evaluate in vivo the potential of 188Re-PEI-MP as therapeutic agent for bladder carcinoma and 99mTc-PEI-MP for its diagnosis and follow up